2019
DOI: 10.1038/s41598-019-55643-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased fibroblast growth factor-21 in chronic kidney disease is a trade-off between survival benefit and blood pressure dysregulation

Abstract: Circulating levels of fibroblast growth factor-21 (FGF21) start increasing in patients with chronic kidney disease (CKD) since early stages during the cause of disease progression. FGF21 is a liver-derived hormone that induces responses to stress through acting on hypothalamus to activate the sympathetic nervous system and the hypothalamus-pituitary-adrenal endocrine axis. However, roles that FGF21 plays in pathophysiology of CKD remains elusive. Here we show in mice that FGF21 is required to survive CKD but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…We found that 379 genes (78.8%) were upregulated, while only 102 genes (21.2%) were downregulated in bioprinted and self-assembled iREC tubules. GO-term analysis revealed enrichment in cellular processes, such as response to fibroblast growth factor and organic anion transport, both of which are relevant to the formation of tubular kidney structures in vivo (figure 4(b)) [45][46][47]. Among the robustly up-regulated transcripts (log 2 FC > 1), we found 34 to be enriched in the kidneys with a median expression level two times higher than in other tissues (figure 4(c)).…”
Section: Bioprinted Self-assembled Tubules Show Upregulated Kidney-specific Functional Genesmentioning
confidence: 99%
“…We found that 379 genes (78.8%) were upregulated, while only 102 genes (21.2%) were downregulated in bioprinted and self-assembled iREC tubules. GO-term analysis revealed enrichment in cellular processes, such as response to fibroblast growth factor and organic anion transport, both of which are relevant to the formation of tubular kidney structures in vivo (figure 4(b)) [45][46][47]. Among the robustly up-regulated transcripts (log 2 FC > 1), we found 34 to be enriched in the kidneys with a median expression level two times higher than in other tissues (figure 4(c)).…”
Section: Bioprinted Self-assembled Tubules Show Upregulated Kidney-specific Functional Genesmentioning
confidence: 99%
“…Although the increase of FGF21 increases the cardiovascular risk, it is necessary for the survival of CKD mice. 54 , 83 , 84 Furthermore, the analysis results of clinical samples of diabetic patients with chronic kidney disease showed that when glomerular filtration rate was high, serum FGF21 levels increased with proteinuria but were relatively low in the kidneys. The elevated levels of FGF21 in patients with DN may be due to the increased secretion of the body for protection purposes under the stimulation of stress responses such as inflammation and oxidative stress.…”
Section: The Relationship Between Fibroblast Growth Factor and Diabetic Nephropathymentioning
confidence: 99%
“…The same brains were used in a previous study showing single immunocytochemical detection of c-Fos protein. 24…”
Section: Intracerebroventricular Injections Of Fgf21mentioning
confidence: 99%
“…AAV8 vectors expressing mouse FGF21 or humanised Renilla reniformis green fluorescent protein (hrGFP) under the control of the CAG promoter (chicken β-actin promoter with the cytomegalovirus immediateearly enhancer) were prepared as described previously. 24,27 In brief, 293 cells were transfected simultaneously with adenovirus helper plasmid, AAV type 8 helper plasmid, and the hrGFP or FGF21 plasmid by calcium phosphate transfection and were maintained for 3 days.…”
Section: Aav Vectorsmentioning
confidence: 99%
See 1 more Smart Citation